Educator's Behavior in a Safe Classroom Atmosphere - Ode Yahyu Herliany Yusuf; Siana Siana; Wa Dasria; Darwia Darwia; Waode Nur Mutmainah (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Educators' efforts to create safe and comfortable classrooms for students, as well as a conducive learning environment in encouraging students to learn actively. A conducive school learning environment is closely related to the quality of student learning. It can be realized that a safe and comfortable class can prevent students from boredom and psychological fatigue. While the class is conducive to students' motivation and endurance in learning. Classroom management is also closely related to the quality of student learning so that it is safer and more comfortable in the learning process in the classroom.